Characterization of Pannexin1, Connexin32, and Connexin43 in Spotted Sea Bass (Lateolabrax maculatus): They Are Important Neuro-Related Immune Response Genes Involved in Inflammation-Induced ATP Release - Sun, Zhaosheng; Xu, Chong; Chen, Yuxi; Liu, Danjie; Wu, Ping; Gao, Qian (Frontiers in Immunology, 2022)
Many immunological diseases can be treated by regulating neurobehavior, in which extracellular ATP is a vital member of endogenous danger-associated molecular pattern (DAMP) signaling molecule that plays a crucial part in innate neuro-related immunity. It is actively released through Pannexin (Panx) and Connexin (Cx) hemichannels from activated or stressed cells during inflammation, injury or apoptosis. In addition to participating in ATP release, Panxs and Cxs also have crucial immune functions. In this study, Pannexin1, three Connexin32 isoforms and Connexin43 were identified and characterized in spotted sea bass (Lateolabrax maculatus), which were named LmPanx1, LmCx32.2, LmCx32.3, LmCx32.7 and LmCx43. Their similar topological structure were discovered by sequence analysis: a relatively unconserved C-terminal region and 4 highly conserved transmembrane (TM) domains, etc. Each extracellular (ECL) region of panx1 has two conserved cysteine residues. Unlike Panx1, each ECL region of Cx32 and Cx43 contain 3 conserved cysteine residues, forming two conserved motifs: CX6CX3C motif in ECL1 and CX4CX5C motif in ECL2. Furthermore, Panx1 and Cx43 share similar genomic organization and synteny with their counterparts in selected vertebrates. Cx32 and CX43 were located in the same locus in fish, but diverged into two loci from amphibian. Moreover, despite varying expression levels, the identified genes were constitutively expressed in all examined tissues. All genes were upregulated by PAMP (LPS and poly (I:C)) stimulation or bacterial infection in vivo and vitro, but they were downregulated in brain at 6 h or 12 h after stimulation. Especially, the three LmCx32 isoforms and LmCx43 were upregulated by ATP stimulation in primary head kidney leukocytes, however downregulation of LmCx32.3 and LmCx43 expression was noted at 12 h. Conversely, ATP treatment inhibited the expression of LmPanx1. Importantly, we showed that the spotted sea bass Panx1, Cx43 and Cx32 were localized on the cellular membrane, and involved in inflammation-induced ATP release. Taken together, our results demonstrated that Panx1, Cx32 and Cx43 are important neuro-related immune response genes involved in inflammation-induced ATP release.